Characterization of pbt genes conferring increased Pb2+ and Cd2+ tolerance upon Achromobacter xylosoxidans A8 - Hložková, Kateřina; Suman, Jáchym; Strnad, Hynek; Ruml, Tomas; Paces, Vaclav; Kotrba, Pavel (Research in microbiology, 2013)
The cluster of pbtTFYRABC genes is carried by plasmid pA81. Its elimination from Achromobacter xylosoxidans A8 resulted in increased sensitivity towards Pb(2+) and Cd(2+). Predicted pbtTRABC products share strong similarities with Pb(2+) uptake transporter PbrT, transcriptional regulator PbrR, metal efflux P1-ATPases PbrA and CadA, undecaprenyl pyrophosphatase PbrB and its signal peptidase PbrC from Cupriavidus metallidurans CH34. Expression of pbtABC or pbtA in a metal-sensitive Escherichia coli GG48 rendered the strain Pb(2+)-, Cd(2+)- and Zn(2+)-tolerant and caused decreased accumulation of the metal ions. Accumulation of Pb(2+), but not of Cd(2+) or Zn(2+), was promoted in E. coli expressing pbtT. Additional genes of the pbt cluster are pbtF and pbtY, which encode the cation diffusion facilitator (CDF)-like transporter and a putative fatty acid hydroxylase of unknown function, respectively. Expression of pbtF did not confer increased metal tolerance upon E. coli GG48, although the protein showed measurable Pb(2+)-efflux activity. Unlike the pbtT promoter, promoters of pbtABC, pbtF and pbtY contain features characteristic of promoters controlled by metal-responsive transcriptional regulators of the MerR family. Upregulation of pbtABC, pbtF and pbtY upon Pb(2+), Cd(2+) and Zn(2+) exposure was confirmed in wild-type Achromobacter xylosoxidans A8. Gel shift assays proved binding of purified PbtR to the respective promoters.
Keywords: Gene Expression Regulation, Bacterial; Drug Tolerance; olovo; kadmium; Escherichia coli; P(1)-type ATPase; Cadmium; multigenová rodina; bakteriální geny; MerR family; Achromobacter xylosoxidans; tolerance léku; Zinc; Metal tolerance; Transcriptional control; stanovení celkové genové exprese; regulace genové exprese u bakterií; Lead; Achromobacter denitrificans; plazmidy; Cloning, Molecular; exprese genu; Genes, Bacterial; klonování DNA; Plasmids; Gene Expression Profiling; Gene Expression; Multigene Family